Locations & levels of public space conflict in the UNESCO World Heritage site, George Town, Penang, Malaysia / Muhamad Ferdhaus Sazali ... [et al.] - Sazali, Muhamad Ferdhaus; Zainol, Halmi; Abdul Rahim, Asyirah; Muhammad, Zikri (2021)
The UNESCO World Heritage Site in Malaysia is in George Town, Penang. Spaces within this Heritage Site hold a wide range of historical values which prohibit unauthorized changes. Traders work on a regular basis in the existing spaces. Meanwhile, the hawkers move from one place to another. However, there are also traders and hawkers who are totally misusing and doing business illegally in the public spaces. Demand for street food activities which are well-known in the study area has been identified as a major factor leading to the public space conflicts. The location of the conflict area has been marked and recorded for a more in-depth study. This is to identify the locations and levels of public space conflict. The space for the public is essential for ensuring the sustainability of the environment.